Associations between paraoxonase-1 activity and therapeutic drug monitoring indicators in schizophrenia patients treated with olanzapine: A cross-sectional study - Wu, Tzu-Hua; Hu, Shu-Chin; Sylfa, Nailis; Liao, Jiahn-Haur; Raza, Ahmad; Chen, Bi-Li; Chen, Chun-Hsin; Lu, Mong-Liang (Journal of psychopharmacology (Oxford), 2025)
Therapeutic drug monitoring (TDM) indicators have been suggested to predict overall outcome responses to olanzapine (OLZ) treatments in terms of efficacy and metabolic syndrome. This study aimed to investigate whether paraoxonase-1 (PON-1) activity can be used to predict schizophrenia patient outcomes. Schizophrenic patients ( = 50) aged between 20 and 65 years who received OLZ treatment were recruited, and their Positive and Negative Syndrome Scale scores, PON-1 activity, and olanzapine drug levels normalized by dose (OLZ/D) and its metabolite N-desmethyl-olanzapine (DMO), together with biochemical parameters, were determined. PON-1 activity and OLZ/D were significantly correlated in 50 patients (correlation coefficient, = 0.355; = 0.0115). There was also a statistically significant correlation between the ratio of PON-1 activity normalized by homocysteine (Hcy) and OLZ/D (correlation coefficient = 0.361; = 0.01) and a significant negative correlation between the ratio of PON-1 activity normalized by Hcy and triglyceride/high-density lipoprotein (TG/HDL; correlation coefficient = -0.328; = 0.02). PON-1 activity can be used as an alternative tool for monitoring TDM through the measurement of OLZ together with its metabolite, DMO, to identify patients who have higher activity. Those who show an optimal response or who have lower activity might have greater cardiometabolic risk under long-term olanzapine treatment. Longitudinal monitoring is warranted to confirm such observations.